2002
DOI: 10.1111/1468-0297.00034
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment Duration, Benefit Duration and the Business Cycle

Abstract: In this paper we study the effects of unemployment benefit duration and the business cycle on unemployment duration. We construct durations for individuals entering unemployment from a longitudinal sample of Spanish men in 1987–94. Estimated discrete hazard models indicate that receipt of unemployment benefits significantly reduces the hazard of leaving unemployment. At durations of three months, when the largest effects occur, the hazard for workers without benefits is twice as large as that for workers with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
142
2
15

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(181 citation statements)
references
References 29 publications
(38 reference statements)
16
142
2
15
Order By: Relevance
“…The variables in x(t) are the same as in the unemployment hazard. Following Bover et al (2002) and García-Perez and Muñoz-Bullón (2011), we use a logistic distribution to model all hazard rates. 11 Moreover, as we are considering competing risks models for both employment and unemployment, exit from a given state needs to be specified as a multinomial logit model with two alternative risks for each state:…”
Section: Empirical Approachmentioning
confidence: 99%
“…The variables in x(t) are the same as in the unemployment hazard. Following Bover et al (2002) and García-Perez and Muñoz-Bullón (2011), we use a logistic distribution to model all hazard rates. 11 Moreover, as we are considering competing risks models for both employment and unemployment, exit from a given state needs to be specified as a multinomial logit model with two alternative risks for each state:…”
Section: Empirical Approachmentioning
confidence: 99%
“…Many empirical studies support this discouraging effect of unemployment insurance on job searches. The jump up in employment around the expiration of unemployment insurance and thus prolonged unemployment duration until the expiration date is reported by many researchers, for example, Moffitt (1985), Katz and Meyer (1990), Poterba and Summers (1995), Green and Riddell (1997), Card and Levine (2000) for the U.S. results, and Carling, Holmlund and Vejsiu (2001), Bover, Arellano and Bentolila (2002), Lalive and Zweimüller (2004), Lalive, Van Ours and Zweimüller (2006), Lalive (2007), and Card, Chetty and Weber (2007) for the European results.…”
Section: Introductionmentioning
confidence: 77%
“…Some authors found a positive correlation between the level of unemployment benefits and the length unemployment [Stetsenko 2003;Bover, Arellano, and Bentotila 2002, data: Labour Force Survey, 1987-1994Røed and Zhang 2003;Arulampalam and Stewart 1995;Belzil 2001;Carroll 2006;Lalive 2007;Røed, Jensen, and Thoursie 2008;Arntz and Wilke 2009;Bieszk-Stolorz and Markowicz 2015b] and in case of disabled people [Dànàcicà and Cîrnu 2014].…”
Section: Literature Reviewmentioning
confidence: 99%